2019
DOI: 10.17219/acem/94147
|View full text |Cite
|
Sign up to set email alerts
|

The Polish Prevalence of Infection in Intensive Care (PPIC): A one-day point prevalence multicenter study

Abstract: Background. Infections in critically ill patients are the main reasons for a lack of therapeutic success and increased mortality in intensive care units (ICUs). There have been many analyses of the incidence of infections in ICUs; however, no large studies of this kind have been conducted either in Poland or in Eastern and Central Europe. Objectives. The aim of the research was to undertake a one-day study of the prevalence of infections in ICUs in Warszawa and the Mazovian region of Poland. Material and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
5
6
0
Order By: Relevance
“…In other Polish observational study VAP (15.5/1000) and CLA-BSI (5/1000) incidence density was higher and CAUTI (1.9/1000) incidence density was lower than in our study [34]. Results of our study were similar to results of other studies when VAP was the most commonly diagnosed DA-HAI [6,8,[10][11][12]15]. Our results showed that clinical presentations of HAIs were more frequent than those found in European Centre Disease Control report (except for CLA-BSI), more frequent than the USA CDC report, yet less frequent than in limited-resource countries (except for CA-UTI) [10,24,25].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In other Polish observational study VAP (15.5/1000) and CLA-BSI (5/1000) incidence density was higher and CAUTI (1.9/1000) incidence density was lower than in our study [34]. Results of our study were similar to results of other studies when VAP was the most commonly diagnosed DA-HAI [6,8,[10][11][12]15]. Our results showed that clinical presentations of HAIs were more frequent than those found in European Centre Disease Control report (except for CLA-BSI), more frequent than the USA CDC report, yet less frequent than in limited-resource countries (except for CA-UTI) [10,24,25].…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, infection risk factors were also found to be present on admission [5,6]. According to published data, over 50% of ICU patients are infected [7,8]. It was also found that DA-HAIs concern about 24.3-27.6% of ICU patients [6,9].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of our studies do not differ significantly from other published studies, which show that the dominant HAIs include pneumonias followed by UTI and CLA-BSI [ 3 , 25 , 26 ]. With regards to the domination of GNB in the pathogenesis of HAIs, the results of our study correspond with the results of the Polish multi-center study (PPIC), where the GNB were responsible for 64.1% of infections, while Gram-positive bacteria accounted for 31.8% of infections, with the percentage of infections caused by fungi being 4.1% [ 18 ]. They also correspond with the results of another Polish multi-center study, where GNB accounted for 69.2% of infections and Gram-positive bacteria accounted for 26.8% [ 27 ].…”
Section: Discussionsupporting
confidence: 87%
“…According to published data, in the last decade, the continuous pre-dominance of HAIs caused by strains of GNB ( A. baumannii, P. aeruginosa, K. pneumoniae ) was observed, among which the percentage of MDR bacteria was very high (in Serbia, 88.9–97%; Egypt, 42.5–92.8%; Greece, 92.9%; India, 35–68%; Poland, 98.36% ( Acinetobacter only), Italy, 66.7%; the U.S., 14.6–73.1%) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. During the same period, the frequency of HAIs with MRSA etiology was variable and amounted to 2.7% in Greece, 4.56% in Egypt, 10% in Poland, 13.8% in France, 25.8% in Spain, and 10.3% in Germany [ 12 , 13 , 17 , 18 , 19 ]. Microbiological analysis of infections (also called “microbiological mapping”), which is the subject of this paper, aims to evaluate the epidemiological situation in the hospital unit and is a necessary element of the proper antibiotic policy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%